PTPRC promoted CD8+ T cell mediated tumor immunity and drug sensitivity in breast cancer: based on pan-cancer analysis and artificial intelligence modeling of immunogenic cell death-based drug sensitivity stratification - Li, Pengping; Wang, Wei; Wang, Shaowen; Cao, Guodong; Pan, Tonghe; Huang, Yuqing; Wan, Hong; Zhang, Weijun; Huang, Yate; Jin, Haigang; Wang, Zhenyu (Frontiers in Immunology, 2023)
Background Immunogenic cell death (ICD) is a result of immune cell infiltration (ICI) mediated cell death, which is also a novel acknowledgment to regulate cellular stressors mediated cell death, including drug therapy and radiotherapy. A comprehensive understanding of the effects of ICD-related genes in drug sensitivity stratification is pivotal in improving chemotherapy and anti-endocrine therapy effects in clinical treatment. Methods ICD-related tumor driver genes (ICD-TDGs) based artificial intelligence (AI) modeling was used to construct drug sensitivity stratification in BRCA, which is trained in The Cancer Genome Atlas (TCGA) data cohort and tested in Gene Expression Omnibus (GEO). Drug sensitivity prediction is performed by the OncoPredict function, based on the genome or 14 ICD-TDGs. Multiple fluorescence staining was used to assess CD8+ T cell infiltration and PTPRC expression. Results This study identified ICD-related pan-cancer subgroups, and ICD-TDGs-based AI modeling was performed to construct drug sensitivity stratification in pan-cancer and breast cancer. Amongst different subgroups, it showed significant gene expression characteristics, prognosis differences, immune cell infiltration features, and drug sensitivity. Unexpectedly, ICD-TDGs-based drug sensitivity prediction was alible to represent the genome-based drug sensitivity prediction, which was further verified in clinical trials (public data). Then, network analysis identified CD8+ T cells were key infiltrated immune cells in ICD-mediated drug sensitivity regulation. Finally, PTPRC was identified as the pivotal one in regulating drug sensitivity in ICD/ICI/drug sensitivity. Through in vitro experiments, we found intracellular down-regulation of PTPRC enhanced paclitaxel tolerance in triple breast cancer (TNBC) cell lines. Meantime, the expression level of PTPRC was positively correlative with CD8+ T cell infiltration.